Perak disturbances 1871-75: British colonialism, the Chinese secret societies and the Malay rulers - Azmi Arifin, (Penerbit UKM, 2012)
This article is a re-interpretation of the history of ‘power struggles’, ‘civil wars’ and ‘anarchy’ which were asserted to have happened in Perak, one of the Malay states in the Malay Peninsula during the period of 1871-75. Up until now, historians tend to suggest that the ‘Malay feudalism’, i.e. the political disputes and the power struggle among the Malay rulers; were the main factors that prompted the Perak 1871-75 mayhem. This writing, however, finds that allegations of ‘civil wars’ and ‘anarchy’; blamed for their so-called roles that pushed Perak to the brink of collapse and eventually led to British intervention, has not been credibly supported. By utilizing authoritative primary and secondary sources, the author argued that these are merely imaginary excuses invented by the British colonial officials to paint the negative perception that the disturbances happened at large in Perak and that the indigenous rule was deteriorating in shape. These excuses were made to simplify justifications by the British in its quest to intervene into the Malay states affairs in the late period of the 19th century.